A new genus of treeshrew and other micromammals from the middle Miocene hominoid locality of Ramnagar, Udhampur District, Jammu and Kashmir, India. (November 2022) - Sehgal, Ramesh Kumar; Singh, Abhishek Pratap; Gilbert, Christopher C.; Patel, Biren A.; Campisano, Christopher J.; Selig, Keegan R.; Patnaik, Rajeev; Singh, Ningthoujam Premjit
Abstract: The fossil record of treeshrews, hedgehogs, and other micromammals from the Lower Siwaliks of India is sparse. Here, we report on a new genus and species of fossil treeshrew, specimens of the hedgehog Galerix, and other micromammals from the middle Miocene (Lower Siwalik) deposits surrounding Ramnagar (Udhampur District, Jammu and Kashmir), at a fossil locality known as Dehari. The treeshrew from Dehari ( Sivatupaia ramnagarensis n. gen. n. sp.) currently represents the oldest record of fossil tupaiids in the Siwaliks, extending their time range by ca. 2.5–4.0 Myr in the region. Dietary analyses suggest that the new tupaiid was likely adapted for a less mechanically challenging or more frugivorous diet compared to other extant and fossil tupaiids. The occurrence of Galerix has only been recently documented from the Indian Siwaliks and the Dehari specimens help establish the likely presence of a relatively large Siwalik Galerix species in the Ramnagar region. In addition to the new treeshrew and hedgehogs, new specimens of the rodents Kanisamys indicus, Sayimys sivalensis, and Murinae indet. from Dehari help confirm that age estimates for the Ramnagar region are equivalent to the Chinji Formation in Pakistan, most likely corresponding to the middle to upper part of the Chinji Formation. UUID: http://zoobank.org/56fb160c-2df8-4cd3-be91-af4dc02d0979